Economic growth in Africa and foreign direct investment - (:unkn) unknown (My University, 2014)
Starting with the first observation that the African continent has been and still is, one whose inhabitants are the poorest in the world, we have assigned a target to try to identify the ins and outs. In light of advances in growth theory, we have listed the two main mechanisms conveyors of economic growth, namely the accumulation of factors of production and technical progress. As second observation, we noticed that both the investment rate and the level of technical progress was lower on the African continent than elsewhere. Also aware of this situation, the governments of these countries have begun to attract more foreign investment as possible, on the one hand considered as a way to circumvent the lack of productive investment and secondly as a mode of adoption of new technologies. Therefore, the impact of FDI on economic growth in developing countries and in Africa in particular, has been the object of our study. We found in our study, as in the literature on the subject, that the impact of FDI on domestic investment in Africa is neutral, supporting the assumption that these investments increase at least the stock of physical capital per head of our African sample. In doing so, the FDI will affect the per capita income of countries in our sample, in different proportions but according to the same principle as the national investments. We found that foreign direct investment, had an average positive upper impact on the long-term level of per capita income (22% average increase every five-year) than domestic investment (0.5% average increase every five-year) . However, we have not registered positives productivity externalities in these countries, due to the presence of foreign business. Within a larger sample this time, including as well developed countries, developing countries and African countries, we found that FDI becomes significant for the process of technological catching-up, by productivity externalities when the ratio of total factor prod
Keywords: African Research